Grey Wolf Optimization based Clustered On – Demand Load Balancing Scheme (GWO-COD-LBS) for Heterogeneous Mobile Ad hoc Networks - Devi, P. Aruna; Karthikeyan, K (International Journal of Computer Sciences and Engineering, 2019)
Load balancing is the research dimension in the field of mobile ad hoc networks. From the several previously conducted research works it is inferred that clustering based load balancing approach offers better solution. Many protocols are proposed formerly, and multipath routing seems to be better one. This research work aims to make use of grey wolf optimization technique for clustering the nodes. Conventional multipath routing strategy is employed along with adaptive load balancing approach. Simulation settings are made and the performance metrics namely packet delivery ratio, throughput, packets drop, overhead and delay are taken into account for evaluating the efficiency of the approach.